Using Ion-Selective Electrodes to Study the Drug Release from Porous Cellulose Matrices - Hossein Vakili; Natalja Genina; Henrik Ehlers; Johan Bobacka; Niklas Sandler (MDPI AG, 2012)
Polyvinyl chloride (PVC)-based solid-contact ion-selective electrodes (SC-ISEs), responding to propranolol hydrochloride (Pr+) and lidocaine hydrochloride (Ld+) cations as the model drugs with potassium tetrakis(4-chlorophenyl) borate (KTpClPB) as the ion exchanger, were studied. Different drug-polymer solutions were prepared with the model drugs, using different blend ratios of ethylcellulose (EC) and hydroxypropyl cellulose (HPC). Two different solid dosage forms were used. Polymer films were produced by solvent casting method and drug containing porous cellulose samples were prepared by depositing the drug-polymer solutions onto filter paper substrates. The quality of the electrodes and the release profile of Pr+ and Ld+ were investigated with the potentiometric method. The results were compared to UV spectrophotometry. The electrodes were found to be sensitive, precise and functional with a Nernstian behavior over the range of 1.0 × 10−3-3.1 × 10−6 M (9.2 × 10−4-3.0 × 10−1 mg/mL) and 1 × 10−3-2 × 10−6 M (5.4 × 10−4-2.7 × 10−1 mg/mL) at 25 °C for Pr+ and Ld+ sensitive electrodes, respectively. The dynamic response time for the electrodes was less than 10 s. The Pr+ release from porous filter paper was always higher than its equivalent film formulation. Also, lidocaine had higher and faster release from the samples with higher drug concentration. The comparison of the two analytical methods showed near identical results. The ISEs provided a powerful and flexible alternative to UV method in determination of drug release from porous cellulose substrates in a small scale dissolution testing.